CC Chemokines in Idiopathic Pulmonary Fibrosis: Pathogenic Role and Therapeutic Potential - Shanshan Liu; Chang Liu; Qianrong Wang; Suosi Liu; Jiali Min (Biomolecules, 2023)
Idiopathic pulmonary fibrosis (IPF), characterized by progressive worsening of dyspnea and irreversible decline in lung function, is a chronic and progressive respiratory disease with a poor prognosis. Chronic or repeated lung injury results in inflammation and an excessive injury-repairing response that drives the development of IPF. A number of studies have shown that the development and progression of IPF are associated with dysregulated expression of several chemokines and chemokine receptors, several of which have been used as predictors of IPF outcome. Chemokines of the CC family play significant roles in exacerbating IPF progression by immune cell attraction or fibroblast activation. Modulating levels of detrimental CC chemokines and interrupting the corresponding transduction axis by neutralizing antibodies or antagonists are potential treatment options for IPF. Here, we review the roles of different CC chemokines in the pathogenesis of IPF, and their potential use as biomarkers or therapeutic targets.